High-entropy alloy with cross-scale non-uniform structure and preparation method of high-entropy alloy

By introducing C or N or B or Si elements into high-entropy alloys, a non-uniform structure across scales is formed, the problem of low strength of existing high-entropy alloys is solved, and the significant improvement of high yield strength and tensile strength is achieved, satisfying the Higher performance material requirements.

CN119243010APending Publication Date: 2025-01-03WUHAN UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411321559.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing face-centered cubic high-entropy alloy has a small room temperature strength, a yield strength of 340~430MPa and a tensile strength of 550~700MPa, which limits its development and application as a structural material.

Method used

A high-entropy alloy with a span scale non-uniform structure is used, and its composition is Fe: 30-40%, Mn: 15-25%, Co: 15-20%, Cr: 15-20%, Ni: 5-10%, Among them, the M element is a composite addition of C or N or B or Si to form a gradient microstructure of a single FCC phase, including a thickness of 85 to 95% of the thickness of crystals, layered structure and precipitates, which are vacuum smelting, homogenized annealing, Preparation of hot rolling, cooling, annealing and aging treatment processes.

Benefits of technology

High-strength and high-toughness and high-performance high-entropy alloys with yield strength between 530 and 920MPa, tensile strength between 850 and 1200MPa, and elongation between 25 and 50%, meeting higher scientific research and industrial application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243010A_ABST
    Figure CN119243010A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy alloy with a cross-scale non-uniform structure. The high-entropy alloy comprises the following components in percentage by weight: 30-40% of Fe, 15-25% of Mn, 15-20% of Co, 15-20% of Cr, 5-10% of Ni and 0-1% of M, the preparation method comprises the following steps: preparing raw materials; smelting in a vacuum furnace; performing homogenizing annealing; air cooling; hot rolling; water cooling; cold rolling to the product thickness; annealing is conducted; aging treatment; and air-cooling to room temperature for later use. A matrix phase is a single FCC phase, the grain size span is large, the structure is a gradient microstructure formed by coarse grains with the average grain size being 9.12-12.45 microns and fine grains with the average grain size being 0.54-2.45 microns, the volume ratio of the coarse grains to the fine grains is 85-95%, the balance is a layered organization structure and precipitates, the yield strength is 530-920 MPa, the tensile strength is 850-1200 MPa, the tensile strength is 850-1200 MPa, and the tensile strength is 850-1200 MPa. The invention discloses a high-entropy alloy with a cross-scale non-uniform structure and a preparation method of the high-entropy alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high entropy alloy and a preparation method thereof, and in particular to a high entropy alloy with a cross-scale inhomogeneous structure and a preparation method thereof. Background Art

[0002] High entropy alloys were first proposed by Yeh et al. in 2004. They are composed of multiple types of elements with large contents. Each element can be used as the main element of the alloy, but this does not make the alloy form a large number of intermetallic compound phases. Instead, it has a simple solid solution structure, and each main element occupies a lattice position in the alloy. The existence of multiple main elements enables high entropy alloys to have high entropy effects in thermodynamics, lattice distortion effects in structure, slow diffusion effects in kinetics, and cocktail effects in performance. They have better properties than traditional alloys, such as high strength and hardness, excellent wear resistance, and outstanding low-temperature and high-temperature characteristics.

[0003] CoCrFeMnNi high entropy alloy is the earliest and most in-depth type of high entropy alloy, and its phase structure is a single face-centered cubic structure. In general, face-centered cubic high entropy alloys have excellent plasticity, but their room temperature strength is relatively low, with a yield strength of 340-430MPa and a tensile strength of 550-700MPa, which seriously hinders their development and application as structural materials. At present, with the development of science and technology, the performance requirements for high entropy alloy materials are getting higher and higher. The development of high-performance alloy materials with high strength and high toughness has become a research hotspot and goal in the field of scientific research and industrial application.

[0004] The patent document with publication number CN113430405B discloses a high-strength and toughness face-centered cubic high-entropy alloy and its preparation method. By adding C element, the mechanical properties of the alloy are improved. Its yield strength is 367-666MPa, its tensile strength is 806-986MPa, and its elongation is 23-48%. Although its plasticity is relatively good, its strength level can be further improved. Similarly, the patent document with publication number CN118186276B discloses a high-entropy alloy and its preparation method. By introducing trace amounts of Al and Si elements, the mechanical properties of the alloy are enhanced. Its tensile strength is 425-902MPa, its elongation is 55-71%, and its plasticity is relatively good, but its strength is low and can be further improved. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of low strength of face-centered cubic high-entropy alloys in the prior art, and to provide a high-entropy alloy with a single FCC phase in the matrix phase and a large grain size span, that is, a gradient microstructure formed by coarse crystals with an average grain size of 9.12 to 12.45 μm and fine crystals with an average grain size of 0.54 to 2.45 μm, the volume ratio of the two being 85 to 95%, and the rest being layered structure and precipitates, a yield strength of 530 to 920 MPa, a tensile strength of 850 to 1200 MPa, an elongation of 25 to 50%, and a preparation method thereof.

[0006] Measures to achieve the above objectives:

[0007] A high entropy alloy with a cross-scale inhomogeneous structure, wherein the components and weight percentage contents are: Fe: 30-40%, Mn: 15-25%, Co: 15-20%, Cr: 15-20%, Ni: 5-10%, M: 0-1%, wherein the M element is a composite addition of one or more of C, N, B or Si; the metallographic structure of the high entropy alloy is a single FCC phase, and the structure of the high entropy alloy is a gradient microstructure formed by coarse crystals with a grain size greater than 9.12 μm and fine crystals with a grain size less than 2.45 μm, wherein the volume ratio of the two accounts for 85-95%, and the rest is a layered structure and precipitates.

[0008] A method for preparing a high entropy alloy having a cross-scale inhomogeneous structure, comprising the steps of:

[0009] 1) Raw materials configuration

[0010] The Fe, Mn, Co, Cr and Ni metal particles with purities higher than 99.9% are weighed according to their respective value ranges, wherein the M element is added in the form of FeM alloy, and the remaining Mn, Co, Cr and Ni are added in the form of raw materials with a purity of not less than 99.9%. Since the M element is added in the form of FeM alloy, this part should be subtracted when calculating the mass of the corresponding pure Fe metal particles, and the Fe content is also not less than 99.9%;

[0011] 2) Melting in a vacuum furnace

[0012] Put the above-prepared raw materials into a vacuum furnace for smelting. During this period: close the vacuum cover and wait until the vacuum degree is ≤5×

[0013] 10 -3 When Pa, argon gas is introduced for stirring and melting; and the whole process is controlled to be repeated for 5 to 6 times; and then cast into an ingot, and the thickness of the ingot is controlled to be 35 to 40 mm;

[0014] 3) Perform homogenization annealing, control the annealing temperature at 1250-1350°C, and keep it at this temperature for 1-2 hours;

[0015] 4) Air cooling to 100-200°C;

[0016] 5) hot rolling, controlling the initial rolling temperature at 1050-1150°C and the final rolling temperature at 950-1050°C;

[0017] 6) Cooling by water cooling to 100-200°C at a cooling rate of 20-30°C / s, and then air cooling to room temperature;

[0018] 7) Cold rolling to product thickness, controlling the rolling passes to 5-6 times, and the cumulative deformation to 70-90%;

[0019] 8) Annealing, controlling the annealing temperature at 600-1000°C, and keeping at this temperature for 0.5-1h;

[0020] 9) Aging treatment is carried out in a vacuum high-temperature tube furnace. When the vacuum degree in the furnace is less than 10 -3 Pa, heating to the aging treatment temperature, the aging treatment temperature is 550-650°C, and the treatment time is 10-12h;

[0021] 10) Air cool to room temperature for later use.

[0022] Preferably, the homogenization annealing temperature is between 1265°C and 1325°C.

[0023] Preferably, the initial hot rolling temperature is between 1075 and 1125°C, and the final rolling temperature is between 965 and 1025°C.

[0024] Preferably, the temperature is cooled to 120-180° C. at a water cooling rate of 24-30° C. / s.

[0025] Preferably, the annealing temperature is between 630°C and 960°C.

[0026] Preferably, the aging treatment temperature is 580-630° C., and the treatment time is 10-11 hours.

[0027] Functions and mechanisms of the components and main processes in the present invention

[0028] Fe: The Fe element has strong structural stability. An appropriate amount of Fe element can improve the structural stability of the FCC phase, while improving the strength and hardness of the alloy. However, too high Fe content may make the alloy brittle and reduce ductility, so the Fe content is controlled within the range of 30-40%.

[0029] Mn: The Mn element has no effect on the microstructure of the alloy, but the yield strength of the alloy first increases and then decreases with the increase of the Mn content. An appropriate amount of Mn content can improve the wear resistance and corrosion resistance of the alloy, as well as the mechanical properties of the alloy. However, too high a Mn content will lead to the formation of a chromium-rich phase, significantly reducing the compressive strength and ductility of the alloy. Therefore, the Mn content is controlled within the range of 15-25%.

[0030] Co: The Co element helps to stabilize the FCC phase. Its effect on the ductility of the alloy is that the ductility first increases and then decreases with the increase of Co content. An appropriate amount of Co content can improve the plasticity and toughness of the alloy, but excessive Co may cause brittle phases or element segregation in the alloy, thereby reducing ductility. Therefore, the Co content is controlled in the range of 15-20%.

[0031] Cr: Cr is an element with strong corrosion resistance. Adding it to high entropy alloys can improve the mechanical properties of the alloys. However, as the Cr content increases, BCC or B2 phases gradually precipitate in the alloy, making the alloy hard and brittle, and the strength and hardness are significantly improved, but the plasticity is greatly reduced. Therefore, the Cr content is controlled within the range of 15-20%.

[0032] Ni: The Ni element plays a role in stabilizing the FCC phase in face-centered cubic high entropy alloys. As the Ni content increases, the stability of the FCC phase generally increases, which helps to maintain the stability of the alloy's crystal structure and reduce the occurrence of phase changes. In FCC phase high entropy alloys, increasing the Ni content can increase the yield strength and tensile strength of the alloy. However, too high a Ni content will lead to reduced plasticity and toughness of the alloy, so the Ni content is controlled within the range of 5-10%.

[0033] Composite addition of one or more of C, N, B or Si: C element is easy to form carbide particles with other elements and precipitate into the alloy, so that the solid solution strengthening effect in the alloy is enhanced, and the strength and hardness are increased; N element precipitates from the matrix phase in the form of MN nitride, which plays a role in pinning dislocations and improves the yield strength and hardness of the alloy; B element is more likely to form hard second phase precipitates, and with the increase of B content, the hardness and wear resistance of the alloy increase linearly; Si element plays a very important role in improving the hardness and wear resistance of the alloy, but with the increase of Si content, the phase structure changes from FCC to BCC. Non-metallic elements such as C, N, B, and Si are often added to high entropy alloys as interstitial / substitutional atoms to improve the mechanical properties of the alloy and achieve a breakthrough in performance. However, excessive element doping usually forms a brittle ceramic phase, which in turn reduces the mechanical properties of the alloy. Therefore, its content is controlled within a range of no more than 1%.

[0034] The present invention closes the vacuum cover during vacuum smelting and waits for the vacuum degree to be ≤5×10-3 When the temperature is 0.04 Pa, argon is introduced for stirring and smelting to prevent the metal from reacting with oxygen at high temperature, thereby avoiding oxidation of the metal or the production of other unwanted compounds.

[0035] The reason why the present invention controls the homogenization annealing temperature at 1250-1350°C and keeps it at this temperature for 1-2 hours is to promote the diffusion of alloy elements, make the chemical composition inside the alloy more uniform, eliminate element segregation, and avoid melting of alloy grain boundaries and burning of main elements due to excessively high temperature or excessively long time, thereby reducing the performance of the alloy.

[0036] The reason why the initial rolling temperature is controlled at 1050-1150° C. and the final rolling temperature is controlled at 950-1050° C. in the present invention is to refine the grains and improve the internal organizational structure.

[0037] The reason why the present invention controls the cooling to 100-200°C at a water cooling rate of 20-30°C / s and then air-cools to room temperature is to refine the grains and eliminate the internal stress generated in the alloy during the rolling process.

[0038] The reason why the cumulative deformation of cold rolling is controlled within 70-90% in the present invention is that the grains are further refined through rolling with a large deformation amount, and a large number of dislocations and grain boundaries are introduced at the same time.

[0039] The reason why the present invention controls the annealing temperature at 600-1000°C and keeps the temperature at this temperature for 0.5-1h is to promote the recrystallization of deformed grains in the alloy and the precipitation of precipitates such as carbides, nitrides, borides, etc.

[0040] The reason why the present invention is that when the vacuum degree in the furnace is less than 10 -3 The aging treatment is carried out at 550-650°C and the treatment time is 10-12h in order to further improve the hardness and strength of the high entropy alloy and improve the microstructure of the alloy.

[0041] Compared with the prior art, the present invention has a single FCC phase as the matrix phase, a large grain size span, a gradient microstructure formed by coarse crystals with an average grain size of 9.12 to 12.45 μm and fine crystals with an average grain size of 0.54 to 2.45 μm, wherein the volume ratio of the coarse crystals and the fine crystals is 85 to 95%, and the rest is a layered structure and precipitates, a yield strength of 530 to 920 MPa, a tensile strength of 850 to 1200 MPa, an elongation of 25 to 50%, and a high entropy alloy with a cross-scale non-uniform structure and a preparation method thereof. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the EBSD diagram of the present invention. DETAILED DESCRIPTION

[0043] The present invention is described in detail below:

[0044] Table 1 is a list of chemical components of various embodiments and comparative examples of the present invention;

[0045] Table 2 is a list of main process parameters of various embodiments and comparative examples of the present invention;

[0046] Table 3 is a table of performance test results of various embodiments and comparative examples of the present invention.

[0047] Each embodiment of the present invention is produced according to the following steps

[0048] 1) Raw materials configuration

[0049] The Fe, Mn, Co, Cr and Ni metal particles with purities higher than 99.9% are weighed according to their respective value ranges, wherein the M element is added in the form of FeM alloy, and the remaining Mn, Co, Cr and Ni are added in the form of raw materials with a purity of not less than 99.9%. Since the M element is added in the form of FeM alloy, this part should be subtracted when calculating the mass of the corresponding pure Fe metal particles, and the Fe content is also not less than 99.9%;

[0050] 2) Melting in a vacuum furnace

[0051] Put the above-prepared raw materials into a vacuum furnace for smelting. During this period: close the vacuum cover and wait until the vacuum degree is ≤5×

[0052] 10 -3 Pa, argon gas is introduced for stirring and melting; and the whole process is controlled to be repeated 5 to 6 times; and then cast into ingots.

[0053] The thickness of the ingot is controlled at 35-40 mm;

[0054] 3) Perform homogenization annealing, control the annealing temperature at 1250-1350°C, and keep it at this temperature for 1-2 hours;

[0055] 4) Air cooling to 100-200°C;

[0056] 5) hot rolling, controlling the initial rolling temperature at 1050-1150°C and the final rolling temperature at 950-1050°C;

[0057] 6) Cooling by water cooling to 100-200°C at a cooling rate of 20-30°C / s, and then air cooling to room temperature;

[0058] 7) Cold rolling to product thickness, controlling the rolling passes to 5-6 times, and the cumulative deformation to 70-90%;

[0059] 8) Annealing, controlling the annealing temperature at 600-1000°C, and keeping at this temperature for 0.5-1h;

[0060] 9) Aging treatment is carried out in a vacuum high-temperature tube furnace. When the vacuum degree in the furnace is less than 10 -3 Pa, heating to the aging treatment temperature, the aging treatment temperature is 550-650°C, and the treatment time is 10-12h;

[0061] 10) Air cool to room temperature for later use.

[0062] Table 1 Chemical composition list of various embodiments and comparative examples of the present invention (wt%)

[0063]

[0064]

[0065] Table 2 List of main process parameters of various embodiments of the present invention and comparative examples

[0066]

[0067] Table 2

[0068]

[0069]

[0070] Table 3 List of mechanical properties test results of various embodiments of the present invention and comparative examples

[0071]

[0072] From the results in Table 3, it can be seen that the high entropy alloy using the composition design and production process of the present invention has good mechanical properties, with a yield strength of 530-920 MPa, a tensile strength of 850-1200 MPa, and an elongation of 25-50%. However, the performance indicators of Comparative Examples 1 and 2, which are not within the design range, are not as good as those of the embodiments and cannot meet industrial needs.

[0073] This specific implementation is only the best example and is not a restrictive implementation of the technical solution of the present invention.

Claims

1. A high entropy alloy with a cross-scale inhomogeneous structure, the composition and weight percentage of which are: Fe: 30-40%, Mn: 15-25%, Co: 15-20%, Cr: 15-20%, Ni: 5-10%, M: 0-1%, where M is C Or one or more of N or B or Si are added in combination; the metallographic structure of the high entropy alloy is a single FCC phase, and the structure of the high entropy alloy is a gradient microstructure formed by coarse grains and fine grains, the volume ratio of which accounts for 85-95%, and the rest is a layered structure and precipitates.

2. A method for preparing a high entropy alloy having a cross-scale inhomogeneous structure as claimed in claim 1, comprising the steps of: 1) Raw materials configuration The Fe, Mn, Co, Cr and Ni metal particles with purities higher than 99.9% are weighed according to their respective value ranges, wherein the M element is added in the form of FeM alloy, and the remaining Mn, Co, Cr and Ni are added in the form of raw materials with a purity of not less than 99.9%. Since the M element is added in the form of FeM alloy, this part should be subtracted when calculating the mass of the corresponding pure Fe metal particles, and the Fe content is also not less than 99.9%; 2) Melting in a vacuum furnace The prepared raw materials are placed in a vacuum furnace for smelting. During this period, the vacuum cover is closed and the vacuum degree is ≤5×10 -3 Pa When the argon gas is introduced for stirring and melting, the whole process is controlled to be repeated for 5 to 6 times, and then cast into an ingot with a thickness of 35 to 40 mm. 3) Perform homogenization annealing, control the annealing temperature at 1250-1350°C, and keep it at this temperature for 1-2 hours; 4) Air cooling to 100-200°C; 5) hot rolling, controlling the initial rolling temperature at 1050-1150°C and the final rolling temperature at 950-1050°C; 6) Cooling by water cooling to 100-200°C at a cooling rate of 20-30°C / s, and then air cooling to room temperature; 7) Cold rolling to product thickness, controlling the rolling passes to 5-6 times, and the cumulative deformation to 70-90%; 8) Annealing, controlling the annealing temperature at 600-1000°C, and keeping at this temperature for 0.5-1h; 9) Aging treatment is carried out in a vacuum high-temperature tube furnace. When the vacuum degree in the furnace is less than 10 -3 Pa, heating to the aging treatment temperature, the aging treatment temperature is 550-650°C, and the treatment time is 10-12h; 10) Air cool to room temperature for later use.

3. The method for preparing a high entropy alloy having a cross-scale inhomogeneous structure according to claim 2, characterized in that: The homogenization annealing temperature is between 1265 and 1325°C.

4. The method for preparing a high entropy alloy having a cross-scale inhomogeneous structure according to claim 2, characterized in that: The initial rolling temperature of hot rolling is between 1075 and 1125°C, and the final rolling temperature is between 965 and 1025°C.

5. The method for preparing a high entropy alloy having a cross-scale inhomogeneous structure according to claim 2, characterized in that: Cool to 120-180°C at a water cooling rate of 24-30°C / s.

6. The method for preparing a high entropy alloy having a cross-scale inhomogeneous structure according to claim 2, characterized in that: The annealing temperature is between 630 and 960°C.

7. The method for preparing a high entropy alloy having a cross-scale inhomogeneous structure according to claim 2, characterized in that: The aging treatment temperature is 580-630°C, and the treatment time is 10-11 hours.

Citation Information

Patent Citations

  • A high-strength and high-toughness face-centered cubic high-entropy alloy and its preparation method

    CN113430405B

  • A high entropy alloy and preparation method thereof

    CN118186276B